Neural network in corner detection of vertex chain code series - Subri, S. H. (2006)
This paper presents a Neural Network Classifier to be implemented in corner detection of chain code series. The classifier directly uses chain code which is derived using Freeman chain code as training, testing and validation set. The steps of developing Neural Network Classifier are included in this paper. Comparison results between Neural Network Classifier corner detection and other computational corner detection are presented to show the reliability of the proposed classifier. This paper ends with the discussions on the implementation of proposed neural network in corner detection of chain code series. Experimental results have shown that the proposed network has good robustness and detection performance. This makes this method a great choice for machine vision.